Assessment of the efficacy of CBCT referral forms at Faculty of Dentistry, International Islamic University Malaysia - Abu Bakar, Noraini (2016)
Introduction: Cone beam computed tomography (CBCT) has gained interest for improving diagnosis, treatment planning and facilitating better patient’s management in various dental fields. This study is part of the quality assurance programme in Dental Faculty, International Islamic University Malaysia (IIUM). This center offers dental radiography service not only for internal clinics but also act as a referral center for the eastern areas, Pahang, Malaysia. Aims: The aims of this study were; 1) to assess referral pattern for CBCT scans at the Dental Faculty, IIUM, Kuantan, and 2) to evaluate the completeness of the current referral form used by clinicians (for both internal and external referrals). Methods: An audit looking at both the external and internal referral CBCT forms of a four year period of examination (2010-2013) at the Radiology Unit, Dental Faculty, IIUM. Source of referrals, indications for CBCT and the referral forms were examined and analysed. Results: Total CBCT scans taken within the four-year period were 171, in which 96 were referred from internal sources whilst 75 were external referrals. External referrals were mainly from Paediatric Dentistry and Orthodontic clinics (59%), while other referrals were from implant clinic (20%), Paediatrics and Special Needs clinic (15%), Oral MaxilloFacial Surgery clinic (4%) and Periodontic clinic (1%) and Oral Medicine Oral Pathology (OMOP) clinics (1%). All forms from external sources are completely filled. In the Internal referral form, 41% of them came with no indication of why CBCT need to be taken. Out of 59% of cases with indications, 33% came from Paediatric Dentistry and Orthodontic department, followed by Oral Surgery department (10%). Implant treatment planning accounted for 7% of cases, Periodontics 4%, Temporo-Mandibular Joint assessment 2% and 1% for Conservative dentistry and Prosthodontic cases respectively and 1% cleft cases. Further analysis of the internal referral forms revealed that only 14% of the forms were filled with complete patients’ details, 40% specified pregnancy status and 67% clearly stated patients’ medical status. Area of interest was not specified in 69% of cases and clinicians’ names were not stated in 94% of the cases. Majority of the forms were completed with clinicians’ signature (99%) and also radiographers’ details (97%). Conclusions: This study indicated that the majority of IIUM CBCT referrals were from internal sources. However, most of the referral forms were not completely filled. The internal form used, therefore, need to be improved and a much firmer referral framework should be in place.